DIFFERENT LEVEL OF LEARNED-HELPLESSNESS AMONG HIGH SCHOOL STUDENTS WITH LOWER GRADE AND HIGHER GRADE IN SALATIGA INDONESIA - Berta Esti Ari Prasetya (Fakultas Keguruan dan Ilmu Pendidikan Universitas Kristen Satya Wacana, 2013)
This research aimed to investigate whether there is any significant difference in the tendency of experiencing learned-helplessness between high school students with lower grade and higher grade in Salatiga, Indonesia. Survey method was used in collecting the data,utilizing Perceived Influence Questionnaire (Holt, 1980) as the instrument of measurement. 317 participants were involved,consisted of 190 of higher grade students and 127 of lower grade students. Mann-Whitney U was used to analyse the data, considering that the data were not normally distributed. This test result showed that there was a significant difference between high school students with higher grade and lower grade (the Mann-Whitney U coefficient of 10,644, with z value of -1795, p <0.05 (p = 0036, 1-tailed)), with students of lower grade tend to be more prone to experience learned-helplessness. Additional results from their subjective perception on their achievement were also discussed and so were the implications of the study.